Actio Pauliana in Bankruptcy Cases Related to The Provision of Credit Facilities with Fiduciary Guarantees (Case Study of Decision Number 17/Pdt.Sus-Actio Pauliana/2023/PN. Niaga.Smg. Jo. No.20/Pdt.Sus.Pailit/2022/PN Niaga Smg.) - Santa, Bagus Ariyanto; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Actio pauliana is a right granted by law to submit a request to the court to cancel all legal actions that are not required to be carried out by the debtor against his assets which the debtor knows that the legal action is detrimental to the creditor, but of course the holder of the liquidus guarantee also has the right to be prioritized when the debtor is declared bankrupt. The type of research in this study is a normative juridical approach method with research data sources using secondary data. The approach method in this study is a statute approach. Data collection techniques use literature studies in journals, books and digital documents. Data analysis techniques used in this study use prescriptive methods. Problems are analyzed using legal protection theory and legal certainty theory. The results of this study indicate that legal protection for fiduciary guarantee holders when a debtor is declared bankrupt is that the guarantee holders of objects have the right to sell the collateral themselves. They seem not to interfere in bankruptcy matters. Take what is their right from the sales income as payment of their receivables, and if there is still a remainder, this remainder is handed over to the inheritance hall. And the judge's consideration in handing down the decision Number 17 / Pdt.Sus-Actio Pauliana / 2023 / PN. Niaga. Smg. Jo. No. 20 / Pdt.Sus.Pailit / 2022 / PN Niaga Smg. which stated that it rejected the Plaintiffs' lawsuit in its entirety because the actions of Defendant I were an exercise of his right to close/pay off his receivables received from the debtor PT Mitra Bersama Realty incasu Abdul Haris (as director), therefore the actions of the debtor PT Mitra Bersama Realty incasu Abdul Haris (as director) and Defendant I were in order to fulfill their respective obligations arising from the agreement, therefore they did not meet the requirements for an actio pauliana lawsuit. Keywords: Actio Pauliana; Bankruptcy; Fiduciary Guarantee.